Research Trends in Communication Science in Southeast Asia Using the “Vosviewer” Application in Scopus-Indexed Journals - Juli Purnawati; Nurbani; Jonner Hasugian (International Journal of Scientific Multidisciplinary Research, 2024)
This study aims to analyze research Trends in the field of communication sciences in Southeast Asia. The research methodology employed is bibliometric analysis using Vosviewer software. Bibliometric analysis is a method used to quantitatively measure and analyze scientific literature. Findings include the development of Trending research topics, patterns of collaboration among researchers, and the geographic distribution of author affiliations. Additionally, there is evident shifting of research focuses in line with contemporary developments and socio-political changes in the region. However, research Trends in Scopus indicate significant interdisciplinary synergy between communication sciences and fields such as nanotechnology, philosophy, and synthetic biology, which enhance both technology and understanding of communication. The conclusions of this study provide a comprehensive overview of research Trends in communication sciences in Southeast Asia. The results serve as a reference for researchers, academicians, and practitioners to understand the dynamics of research development and identify areas requiring further exploration in Southeast Asian context